2016
DOI: 10.7567/apex.9.052002
|View full text |Cite
|
Sign up to set email alerts
|

GaAs-based triangular barrier photodiodes with embedded type-II GaSb quantum dots

Abstract: We fabricate GaAs-based triangular barrier photodiodes (TBPs), in which type-II GaSb quantum dots (QDs) are embedded in the vertex part of their triangular barriers. Their current–voltage characteristics and photo-responses are studied at low temperatures to show that GaSb QDs enhance the number and lifetime of photo-generated holes that are trapped by QDs in the barrier, resulting in the increase in the electron current around positively charged QDs. An extremely high responsivity of 109 A/W is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…As a result, the barrier height of TBPs can be more precisely controlled by adjusting both the bias voltage and the accumulation of photogenerated holes; consequently, the responsivity of the TBP becomes typically about ten times larger than that of conventional phototransistors. [3][4][5][6][7] In recent works, we studied new types of TBPs in which quantum rods or dots are embedded in the barrier region of GaAs-based TBPs 8,9) and demonstrated that the detector performances can be greatly improved. In this work, we report on the fabrication and evaluation of InGaAs-based TBPs to show that they function as NIR=SWIR detectors with very high responsivity.…”
mentioning
confidence: 99%
“…As a result, the barrier height of TBPs can be more precisely controlled by adjusting both the bias voltage and the accumulation of photogenerated holes; consequently, the responsivity of the TBP becomes typically about ten times larger than that of conventional phototransistors. [3][4][5][6][7] In recent works, we studied new types of TBPs in which quantum rods or dots are embedded in the barrier region of GaAs-based TBPs 8,9) and demonstrated that the detector performances can be greatly improved. In this work, we report on the fabrication and evaluation of InGaAs-based TBPs to show that they function as NIR=SWIR detectors with very high responsivity.…”
mentioning
confidence: 99%